Pengaruh Variasi Temperature dan Media Pendingin Pada Single Screw Plastic Extruder Machine Terhadap Dimensi Diameter Filamen 3D Printing Dengan Material Plastik ABS - Firza Nurdin Maulana; Nurlia Pramita Sari; Agus Hardjito; Subagiyo Subagiyo (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
3D printing technology is rapidly developing and being used in various fields. One of the main factors affecting print quality is the filament, with ABS being a popular material due to its eco-friendliness, ease of printing, and good mechanical strength. To achieve precision, the filament diameter must be consistent, around 1.75 mm or 2.85 mm according to the design nozzle diameter. The production of ABS filament uses a single screw plastic extruder machine, where the material is melted, extruded, and then cooled. Two main factors that affect the final dimensions are the extrusion temperature and the cooling medium. Improper temperature can alter the viscosity of ABS melt, affecting the extrusion rate and diameter accuracy. Meanwhile, differences in cooling media, such as blower air and water, affect material shrinkage and dimensional stability. This research aims to analyze the influence of extrusion temperature variations and cooling media on the diameter of ABS filaments. Through experiments with varying parameters, the pattern of diameter changes will be analyzed to determine the optimal conditions that minimize dimensional deviations. The research results are expected to contribute to the optimization of ABS filament extrusion parameters to support the 3D printing industry with higher quality materials.